Storytelling in Sixteenth-Century France : negotiating shifting forms - Thompson, Emily E.; DellaNeva, JoAnn; Ffolliott, Sheila; Monroe, Amy Graves; LaGuardia, David; Loysen, Kathleen; Polachek, Dora E.; Rothstein, Marian; Usher, Phillip John; Winn, Colette H. (Early modern exchange., 2022)
Storytelling in Sixteenth-Century France is an innovative, interdisciplinary examination of parallels between the early modern era and the world in which we live today. Readers are invited to look to the past to see how then, as now, people turned to storytelling to integrate and adapt to rapid social change, to reinforce or restructure community, to sell new ideas, and to refashion the past. This collection explores different modalities of storytelling in sixteenth-century France and emphasizes shared techniques and themes rather than attempting to define narrow kinds of narrative categories. Through studies of storytelling in tapestries, stone, and music as well as distinct genres of historical, professional, and literary writing (addressing both erudite and more common readers), the contributors to this collection evoke a society in transition, wherein traditional techniques and materials were manipulated to express new realities. Published by the University of Delaware Press. Distributed worldwide by Rutgers University Press.